2014
DOI: 10.5935/0034-7280.20140080
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of macular hole after pars plana vitrectomy: report of two cases

Abstract: The spontaneous closure of a full-thickness macular hole (MH) developed after vitrectomy is very uncommon. We report a small series of cases (two patients) with this presentation. The first patient developed a MH 1 month after vitrectomy for an epirrretinal membrane and, the second one, 3 weeks after vitrectomy for rhegmatogenous retinal detachment. The MHs resolved spontaneously 2 months and 1 month after their documentation by optical coherence tomography(OCT), respectively. In this case report, we review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…4 Meanwhile, Suzuki et al suggested that the process of resolving FTMH could be related to the degeneration of the inner retinal layers due to either atrophy or coalescence of cystoid edema. 5 Ishida et al mentioned that a PVD with release of vitreomacular traction plays an important role for spontaneous closure of the MH. 6 The current gold standard to diagnose MH is via OCT, which is widely available.…”
Section: Discussionmentioning
confidence: 99%
“…4 Meanwhile, Suzuki et al suggested that the process of resolving FTMH could be related to the degeneration of the inner retinal layers due to either atrophy or coalescence of cystoid edema. 5 Ishida et al mentioned that a PVD with release of vitreomacular traction plays an important role for spontaneous closure of the MH. 6 The current gold standard to diagnose MH is via OCT, which is widely available.…”
Section: Discussionmentioning
confidence: 99%